The war of terror : An Analysis of Recent Terrorist Attacks in Two Indonesian News Media - Prayudi - (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2008)
This paper analyses how different Indonesian mass media represent issues of terrorism within an Indonesian context. Mass media and issue of terrorism are inseparable. The representation of terrorism in the Indonesian mass media is the result of a complex construction process which incorporates cultural, political economic and industrial factors. Particularly, it is very much influenced by the rise of the idea of civil society. It has also driven the new idea of freedom of the press in Indonesia. The press becomes more critical in reporting an issue. Media policies also experienced significant changes. Government communication policy only regulates the press in order to ensure they obey codes of ethics and law. To this extent, controversial and highly significant events like the recent terrorist attacks and the international ‘war on terror’ are managed and represented according to the internal policies of the media organizations, rather than the directives of government. At the same time, the mass media has to consider various factors in reporting the issue as terrorism is a sensitive and potentially divisive issue. In this research, the mass media to be analysed includes two national news media with two different perspectives: the Jakarta Post and Sabili. Within each of these news publications, the cultural, political economic and social conditions are treated differently in constructing news. It is assumed that each news publications will report the issue of terrorism and the specific events under review differently.